Saberes tradicionais das mulheres quilombolas: ancestralidade, identidade e memória na comunidade do Córrego do Alexandre – Conceição da Barra/ES - Plotegher, Beatriz Rodrigues (2023)
The objective of this study is to investigate the traditional knowledge of quilombola women in order to understand how and if this knowledge strengthens quilombola identity, memory and ancestry in the Córrego do Alexandre community. From the investigation of this traditional knowledge, understand whether the quilombola community of Córrego do Alexandre and, particularly, the quilombola women of the community perceive this knowledge as traditional, and whether this traditional knowledge was passed on intergenerationally, as we believe that the perpetuation of this knowledge transmitted between the components of a traditional people that transcends generations, reconstituting their practices and ways of being, is a form of resistance and preservation of quilombola culture, even if this knowledge has been modified and/or given new meanings by current generations. The community of Córrego do Alexandre is located in the district of Cricaré, municipality of Conceição da Barra, and is part of the quilombola territory of Sapê do Norte. This territory occupies areas of the municipalities of Conceição da Barra and São Mateus, both in the extreme north of the state of Espírito Santo. The community is certified and legally recognized by the Fundação Cultural Palmares (FCP), as a quilombola community. Methodologically, through a circle of women and semi-structured interviews, we investigated the traditional knowledge of quilombola women in the community by listening to these women. Valuing traditional quilombola knowledge and not letting it fall into oblivion, conjecturing the protagonism to whom it is due, is essential to preserving the ancestry, identity and memory of the quilombola territory of Sapê do Norte.